2023
DOI: 10.1002/jmv.28534
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of monkeypox/mpox virus: A narrative review of environmental, viral, host, and population factors in relation to the 2022 international outbreak

Abstract: Monkeypox virus (MPXV) has spread globally. Emerging studies have now provided evidence regarding MPXV transmission, that can inform rational evidence-based policies and reduce misinformation on this topic. We aimed to review the evidence on transmission of the virus. Real-world studies have isolated viable viruses from high-touch surfaces for as long as 15 days. Strong evidence suggests that the current circulating monkeypox (mpox) has evolved from previous outbreaks outside of Africa, but it is yet unknown w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…Being a DNA virus, mpox is more stable in nature and may have possibly evolved as a potent virus causing infections in humans in the due course of time [ 17 ]. Daniel et al reported 6–12 times higher mutation rates in mpox as previously estimated [ 6 ]. Human to human transmissibility of mpox has also evolved in these decades [ 21 , 22 ].…”
Section: Mpox Outbreak 2022mentioning
confidence: 52%
See 3 more Smart Citations
“…Being a DNA virus, mpox is more stable in nature and may have possibly evolved as a potent virus causing infections in humans in the due course of time [ 17 ]. Daniel et al reported 6–12 times higher mutation rates in mpox as previously estimated [ 6 ]. Human to human transmissibility of mpox has also evolved in these decades [ 21 , 22 ].…”
Section: Mpox Outbreak 2022mentioning
confidence: 52%
“…Vertical infection of mpox has been also reported. Pregnant mothers infected with mpox had miscarriages during the first trimester of pregnancy [ 6 ]. Perinatally acquired mpox infection was registered in a 9-day year old neonate as well [ 23 ].…”
Section: Mpox Outbreak 2022mentioning
confidence: 99%
See 2 more Smart Citations
“…Forward to 2022, when signifi cant local human clusters of mpox were reported in Europe and the United States, [3][4][5][6] these outbreaks were characterized by direct human-to-human transmission. The initial source of these infections is not clear, but unique demographic and clinical characteristics of the infected persons are apparent.…”
mentioning
confidence: 99%